Prescription Drugs Price Setting and Generic Drugs Prescription concerning Consumer Protection Law in Indonesia - Jenny Jatemin; Jovita Irawati (Universitas Pelita Harapan, 2021)
Health is one of the most important human rights in human life. Access to affordable prescription drugs is still a problem for people with out-of-pocket expenses. Generic prescription drugs that are much cheaper than non-generic drugs are still low, especially in non-government healthcare facilities. This research aims to provide suggestions of regulation on price control of prescription drugs and generic prescription drugs that will assure certainty and affordability for the public. The methodology is doctrinal legal research and is supported by empirical studies. The research finding consist of two things, namely the price of prescription drugs and the prescription of generic drugs. The first finding is that Highest Retail Price (HET) set by the manufacturer is potentially to be unlimited because there is no limit control. Currently, there are many drugs sold over HET with minimal supervision from the Government. The absence of law is found as the existing regulations are only for those listed in the National Formulary, while the rest have not been regulated. Therefore, the suggestion is to set ceiling prices for prescription drugs with comparison among generic drugs, branded generic drugs, and the originator; also create a refund mechanism for prices above HET to assure the consumers’ rights to get compensation under the Consumer Protection Law. The second finding is that only a few doctors prescribe generic drugs. Additionally, patients have not been involved in the treatment decisions.Therefore, the suggestion is to associate